Pola Fatwa Dewan Syariah Nasional terhadap Produk Lembaga Keuangan Syariah - Maghfur, Arif (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The National Sharia Council or commonly abbreviated as DSN is an institution under the auspices of the Majlis Ulama Indonesia. The existence of the DSN-MUI institution is to provide legal fatwas related to Islamic Financial Institutions in Indonesia. The increasing number of problems that exist in Islamic Financial Institutions in Indonesia has made DSN-MUI work hard to be able to provide legal fatwas in accordance with the new products submitted by Sharia Banks. This will continue and develop in accordance with the development of the banking world in Indonesia in particular. Therefore, DSN-MUI as an institution in charge of screening and issuing legal fatwas must be able to provide legal fatwas that are truly in accordance with the understanding of the law in Indonesia. DSN-MUI as an institution that has the right to provide law on Islamic financial products still receives a lot of criticism from various circles, both academics and several fiqh law experts. Among these criticisms is the inconsistency of the DSN-MUI fatwa with the literature of the salaf book, which is currently still a reference for most Indonesia scholars. There are also those who criticize the problem of using fiqh rules. DSN-MUI only uses one rule as a legal basis and does not use other rules, even though other rules are related to these rules. Not to mention the use of verses of the Qur'an, which actually have no connection with the law of the product being fatwad. The existence of these criticisms is not to weaken DSN-MUI, but it is hoped that it can be a reinforcement for DSN-MUI, because what they have fatwa will be a reference for many people in muamalah.